KULIAH KERJA MAHASISWA (KKM) di MASA PANDEMI COVID-19 SEBAGAI SALAH SATU BENTUK PENGABDIAN KEPADA MASYARAKAT - Rehulina Tarigan (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
The pandemic not only presents anxiety about health threats, but also the welfare of many employees due to layoffs. Some of small, medium and even large scale businesses were forced to go out of business. Universita Banten Jaya immediately responded positively to the impact that emerged in the community due to the Covid-19 pandemic by holding a Student Work Lecture with the theme